Divorcing a Dangerous Couple - Dow Chemical Company (1938)
Color print advertisement for Dowtherm, a heat transfer fluid manufactured and sold by the Dow Chemical Company. The advertisement features an illustrated depiction of a temperature and a pressure gauge, with accompanying text detailing the use of Dowtherm as a high temperature heat transfer medium in a variety of manufacturing fields, including rubber, petroleum, paints, and varnishes.
Keywords: Dow Chemical Company; Chemical industry; Corporations; Advertising; Advertising, Industrial; Heat; Temperature